Fault classification system for switchgear cbm from an ultrasound analysis technique using extreme learning machine - Ishak S.; Yaw C.T.; Koh S.P.; Tiong S.K.; Chen C.P.; Yusaf T. (MDPI, 2023)
Classification (of information); Computer aided diagnosis; Decision making; Graphical user interfaces; Knowledge acquisition; Machine learning; Maintenance; Neural networks; Ultrasonic applications; Analysis techniques; Classification system; Condition; Condition based maintenance; Decisions makings; Diagnostic tests; Fault classification; Faults diagnosis; Training process; Ultrasound data